Delving into Listening Learning Strategies for Society 5.0 EFL Learners - Manggolo, Noor Sahid Kusuma Hadi; Yunianti, Sukma Shinta; Arifin, M. Fatkhu (ETERNAL (English, Teaching, Learning and Research Journal), 2025)
This study investigates English as a Foreign Language (EFL) learners' listening comprehension strategies using a mixed-methods approach to offer a comprehensive understanding of their practices. The research involved 105 EFL students from Universitas Tidar, Indonesia, employing both quantitative questionnaires and qualitative semi-structured interviews. The questionnaire gathered numerical data on strategy usage, while interviews provided deeper insights into students' experiences and perceptions about the preferences of learning strategy(es). The findings reveal a strong fondness for cognitive strategies. Listening to music and watching movies with subtitles were highlighted as popular and frequently employed methods, illustrating their effectiveness in enhancing listening skills. These strategies were notably discussed more in interviews than reported in questionnaires, suggesting that students might underreport their use in structured formats. Digital tools and applications also emerged as a moderately used strategy, reflecting an increasing integration of technology in language learning. However, advanced strategies, such as watching movies without subtitles or engaging with native speakers, were less commonly used. This indicates potential areas for development, particularly in fostering confidence and proficiency in more challenging listening tasks. The study underscores the importance of a multifaceted approach to language instruction, combining traditional and innovative methods to accommodate diverse learning styles. Educators are encouraged to address the gaps in advanced strategies while leveraging the effectiveness of preferred cognitive and digital tools to enhance EFL learners' listening skills in the context of Society 5.0.